THE SOCIAL MEDIA ALGORITHMS & PERSONAL DATA PROTECTION: THE COMPARATIVE STUDY OF EUROPEAN UNION, CHINA & INDONESIAN LAW - Setianingrum, Reni Budi; Nur Dewata, Mukti Fajar; Mashdurohatun, Anis (Jurnal Pembaharuan Hukum, 2024)
The social media utilize algorithms to increase productive and targeted promotions which regulate the flow of information circulating in the system, and usually record user habits and monitor their personal activities for business profits. This phenomena raise issues amongst academia about the importance of user confidentiality governance in social media. This research is a normative research using conceptual approach and statutory approach, aims to examine whether an algorithms system breach of personal data protection law in European Union, China and Indonesia. The result of this research is the use of algorithm is not explicitly prohibited in European Union States, China and Indonesian Law. Normatively, algorithms utilization do not breach the data protection law in these three countries as long as it uses with user permission, uses for legal reason, provide explanation and protection to the user personal data.